Liberalization and universal access to basic service : (The World Bank, 2006)
Access to basic services plays an important role in both individual well-being and a country's economic development. For this reason, general availability of these services to citizens - regardless of income level and geographic location - has generally been viewed as an important public policy goal. A major challenge for developing countries today is to ensure that achieving greater efficiency through liberalization goes hand in hand with the pursuit of social goals. Building on a recent groundbreaking OECD/World Bank seminar, this volume explores whether and how trade liberalization can contribute to achieving universal service goals and the types of complementary policies required. It focuses on experiences in four sectors - telecommunications, water and sanitation, financial services, and electricity. The unique multi-sector perspective taken in this book, together with the national case studies, yield insights which can help countries promote their universal access goals. A horizontal assessment also helps determine how far the current services negotiations in the WTO, under the General Agreement on Trade in Services, can aid the attainment of universal service goals.